(untitled) (Asian Education Studies, 2022)
With the development and implementation of the national policy of double reduction, for elementary school physical education, if we can effectively use the ecological physical education resource environment to carry out orienteering, it is a lifelong benefit to students’ physical exercise, students can relax more happily in the ecological environment, the natural good ecological environment is more conducive to the healthy development of students’ body and mind, and at the same time can effectively It can also effectively relieve the academic pressure of students in the cultural classroom, thus allowing students to learn more efficiently. The introduction of orienteering in the elementary school physical education classroom has greatly increased students’ awareness of integrating into nature and protecting nature, as well as continuously improving students’ physical fitness and athletic ability, effectively cultivating students’ sports interests and specialties, and continuously using ecological physical education teaching concepts and teaching methods to guide students, so that students have sports skills in line with their own interests and hobbies, and improving students’ sports ability.